2007
DOI: 10.1021/je600565m
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and Density of Water + Ethyl Acetate + Ethanol Mixtures at 298.15 and 318.15 K and Atmospheric Pressure

Abstract: The viscosities and densities of the ternary mixtures water + ethyl acetate + ethanol and their constituent binaries have been measured at 298.15 and 318.15 K and atmospheric pressure. The excess molar volumes, V m E , and viscosity deviations, ∆η, were calculated from density and viscosity, respectively. A rational function due to Myers and Scott was used to describe the composition dependence of these properties. To describe the ternary system, binary pair additivity and the Pando et al. rational functions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 22 publications
10
34
0
Order By: Relevance
“…In relation to the apparent viscosity magnitude, an increase in this value is observed when the ethanol concentration increases in the mixture. This behaviour is due to the addition of ethanol to pure water, which also produces an increase in viscosity (Pires, Costa, Ferreira, & Fonseca, 2007) until a maximum. For this reason, the increase in viscosity shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In relation to the apparent viscosity magnitude, an increase in this value is observed when the ethanol concentration increases in the mixture. This behaviour is due to the addition of ethanol to pure water, which also produces an increase in viscosity (Pires, Costa, Ferreira, & Fonseca, 2007) until a maximum. For this reason, the increase in viscosity shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, structural contributions arising from geometrical fitting of one component into the other because of differences in the free volume and molar volume between components lead to a overall negative contribution to V m E . Here in the present mixtures, it may be concluded that the chemical or specific intermolecular interactions dominate over the other types of interactions [23,24].…”
Section: Excess Acoustical and Thermodynamic Parametersmentioning
confidence: 57%
“…The fluid surface tension, viscosity and density values are listed in Table 1 for different mixtures. These properties are obtained from published physical properties for water–ethanol mixtures 24, 25. Since the changes on fluids viscosities and density are relatively small, the effects of viscosity and density on the spray characteristics and atomisation are expected to be minor.…”
Section: Experimental System and Techniquesmentioning
confidence: 99%